HIGH PRECISE EFFECTIVE TEMPERATURES OF 182 MAIN SEQUENCE STARS - Belik, S. I.; Kovtyukh, V. V.; Yasinskaya, M. P. (Одеські астрономічні публікації, 2008)
High precise temperatures (σ = 10 - 15 K) have been determined from line depth ratios for a set of 182 F-K field dwarfs of about solar metallicity (-0.5 < [Fe/H] < +0.4), based on high resolution (R=42 000), high S/N echelle spectra.